Adapting Meaning-Centered Psychotherapy for the palliative care setting: Results of a pilot study. (February 2017) - Rosenfeld, Barry; Saracino, Rebecca; Tobias, Kristen; Masterson, Melissa; Pessin, Hayley; Applebaum, Allison; Brescia, Robert; Breitbart, William
Aims: To establish preliminary evidence for the feasibility, acceptability, and utility of an abbreviated version of Meaning-Centered Psychotherapy tailored to the needs of palliative care patients in the final weeks or months of life. Background: Surprisingly, few mental health interventions have specifically targeted the psychological needs of palliative care patients, when physical comfort seems to take precedence over mental health and emotional needs. Yet the need for mental health services targeting these patients is clear, as one in three palliative care patients experience clinically significant depression and an equal proportion experience clinically significant anxiety. Design: This pilot study used an open-label design to assess the feasibility, acceptability, and perceived utility of Meaning-Centered Psychotherapy–palliative care, a brief intervention that focuses on enhancing meaning at the end of life. Setting/participants: A total of 12 patients admitted to a palliative care hospital for supportive care consented to participate in the study. Results: Of the 11 patients that began treatment (one patient died before the first session), 8 completed the three-session intervention. Patients expressed positive feedback about the structure, focus, and length of the intervention, but varied in precisely which elements they found most helpful. Conclusion: An abbreviated version of Meaning-Centered Psychotherapy tailored to the needs of palliative care patients (Meaning-Centered Psychotherapy–palliative care) appears to be feasible, acceptable, and has the potential to help patients better cope with the challenges inherent in confronting death and dying. Further research, with larger and more representative samples, is needed in order to clarify the strengths and weaknesses of this approach.